The Genesis of the Askartor Be-Mo Deposit in the North Xinjiang, Northwest China: Evidence From Geology, Geochemistry, U-Pb, and Re-Os Geochronology - Yong, Tang; Hui, Zhang; Zheng-Hang, Lv (Frontiers in Earth Science, 2021)
The Askartor Be-Mo deposit is located in the southeastern area of the Chinese Altay orogenic belt in Xinjiang, NW China. Zircon U-Pb data show that there are two periods of magmatic activities in the Askartor Be-Mo ore district, namely, the Devonian granodiorite (386.8 ± 2.6 Ma) and biotite granite (385.4 ± 4.4 Ma), and the Triassic two-mica granite (247.5 ± 2.2 Ma) and muscovite granite (231.4 ± 2.0 Ma). The zircon U-Pb age of pegmatoid orebody is 220.6 ± 1.6 Ma which coincides with the molybdenite Re-Os isochron age of 228.7 ± 7.1 Ma. The two-mica and muscovite granites belong to the high-K Calc-alkaline series with peraluminous features, and are characterized by high SiO2 (71.92–75.41 wt%), and Al2O3 (13.43–15.98 wt%), and low TiO2 (0.01–0.25 wt%), Fe2O3 (0.11–1.14 wt%) and CaO (0.07–0.76 wt%). The highly fractionated element ratios of Y/Ho, Zr/Hf and Nb/Ta, and the rare earth element tetrad effect occur in the muscovite granite, indicating the fluid exsolution occurs at the late stage of magma evolution, and the muscovite granite experienced the strong self-metasomatism. Rayleigh fractional calculations show that the Askartor Be-Mo deposit is the product of multistage fractional crystallization of initial Be-enriched magma.